2017
DOI: 10.1186/s13104-017-2989-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of MTBDRplus assay in detecting multidrug resistant tuberculosis at hospital level

Abstract: ObjectiveMultidrug-resistant tuberculosis (MDR-TB) case finding progressively increased in Ethiopia mainly as a result of the utilization of World Health Organization (WHO)-endorsed rapid technologies including MTBDRplus assay. However, there is inadequate data on routine testing performance of the MTBDRplus assay. Consequently, the aim of the study was to assess the routine performance of the MTBDRplus assay in detecting MDR-TB at St. Peter’s TB Specialized Hospital.ResultsThe sensitivity and specificity of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 16 publications
1
19
6
Order By: Relevance
“…The sensitivity of GenoType MTBDR plus assay for detection of INH resistance in the present study was lower than those reported by previous studies in Ethiopia, 48 , 51 Uganda 55 and Pakistan. 49 The MTBDR plus assay was not able to detect the INH resistance in the two isolates, which were detected by MGIT 960 system.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…The sensitivity of GenoType MTBDR plus assay for detection of INH resistance in the present study was lower than those reported by previous studies in Ethiopia, 48 , 51 Uganda 55 and Pakistan. 49 The MTBDR plus assay was not able to detect the INH resistance in the two isolates, which were detected by MGIT 960 system.…”
Section: Discussioncontrasting
confidence: 92%
“… 47 This isolate, in addition, missed WT katG gene and developed katG MUT2 with an amino acid change of S315T2 (AGC→ACA). Similarly, such rpoB gene mutation types were observed at low frequency in studies conducted in Ethiopia 48 and Pakistan, 49 and at high frequency in a study conducted in East Hungary. 50 The amino acid change of S315T2 (AGC→ACA) in this isolate was not previously reported from Ethiopia but the most common reported amino acid change in Ethiopia has been S315T1, which is in the range of 83%–100%.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations